Cinnamomum phoebe, a new name for the extant C. elongatum (Lauraceae) - Doweld, Alexander Borisovitch (Phytotaxa, 2016)
The International Fossil Plant Names Index (IFPNI, 2014 onwards) lists some fossil plant species names which have precedence over homonymic extant species names. A few cases of the homonymy between extant and fossil species were recently resolved (Turner 2014, Doweld 2015a, 2015b, 2015c, 2015d).